Resisting the managed and fragmented selves in academia: Collaborative autoethnographies about modulations of control and surveillance in the neoliberal classroom. (September 2021) - Hager, Tamar; Peyrefitte, Magali
Abstract: In this article, we share our personal stories across borders to demonstrate the harm neoliberal governmentalities, in higher education institutions in the UK and Israel, have inflicted on us in our daily teaching routine. Following Sara Ahmed's statement that "[f]eminism as a collective movement is made out of how we are moved to become feminists in dialogue with others" (Ahmed, 2017, p. 5 ), we, as feminist academics, have been cooperating by employing collaborative autoethnography, which enables us to share our personal challenges in teaching in order to confront the surveillance and the individualizing nature of an increasingly neoliberal academia. Analyzing our personal stories in dialogue allows us to better understand the unspoken experiences rooted in emotional and affective encounters between lecturers and students, among lecturers and with the neoliberal academic system as such. Considering the dangers of academic neoliberalism, this article outlines ways of resistance.